2019
DOI: 10.1021/acs.jpcc.9b09932
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Phase Transitions in Densely Packed Nanocrystallites of TiO2-II

Abstract: Phase behaviors of nanocrystalline TiO2-II have not been well studied due to the difficulty in its preparations at ambient pressure. In this work, we prepared nanocrystallites of TiO2-II with average sizes of ∼10–20 nm via high-pressure processing of anatase particles in a large volume press. X-ray diffraction (XRD) and electron microscopy examinations show that the TiO2-II nanocrystallites formed from cracking and phase transformation of large anatase particles under compression. The high-pressure phase behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…At high pressure, the layers of vdW crystals may slide with respect to each other due to the presence of shear stress, leading to cleavage of the crystals and formation of laminates. At high pressure, crystals may also be pulverized to form nanocrystals, as observed in TiO 2 -II, 60 high-entropy diborides, 61 and Lcystine. 62 The electron microscopy images of two CuP 2 Se samples quenched from ∼27 and 52 GPa (Figure 7) indeed show features of layer sliding (Figure S11) that formed lots of sample laminates (Figure 7c).…”
Section: ■ Experimental and Computational Detailsmentioning
confidence: 99%
“…At high pressure, the layers of vdW crystals may slide with respect to each other due to the presence of shear stress, leading to cleavage of the crystals and formation of laminates. At high pressure, crystals may also be pulverized to form nanocrystals, as observed in TiO 2 -II, 60 high-entropy diborides, 61 and Lcystine. 62 The electron microscopy images of two CuP 2 Se samples quenched from ∼27 and 52 GPa (Figure 7) indeed show features of layer sliding (Figure S11) that formed lots of sample laminates (Figure 7c).…”
Section: ■ Experimental and Computational Detailsmentioning
confidence: 99%
“…A higher energy barrier could be a result of either lower Δ G v or higher Δ G s , or both of them. For a specific phase transition (e.g., Si-I → II) at a given pressure, the change of Δ G v in nanomaterials (compared with their bulk counterpart) is mainly determined by the surface/interfacial energy. , Therefore, for the large SiNPs (average size ∼100 nm) and SiNWs (average width ∼100 nm, thickness ∼40 nm) with similar specific surface area in this study, their Δ G v of the Si-I → II transition should be comparable. As a consequence, a possible explanation for the different phase transitions in SiNWs (compared with those in large SiNPs) is that the misfit strain energy Δ G s in SiNWs is higher than that in the SiNPs, resulting in a higher energy barrier for the Si-I → II transition.…”
Section: Discussionmentioning
confidence: 69%
“…Machon et al revealed that rutile TiO 2 NRs showed the same phase transitions as anatase NPs under pressure, i.e., rutile transformed into a disordered baddeleyite structure by compression, and the baddeleyite structure changed into the α-PbO 2 structure upon decompression . Zhang et al investigated the high-pressure phase behaviors of TiO 2 -II nanocrystallites, which displayed two parallel phase transition routes: TiO 2 -II → baddeleyite → TiO 2 -OI and nano TiO 2 -II → TiO 2 -OI . The TiO 2 -II → baddeleyite phase transition pressure decreases with decreasing particle sizes, which is attributed to a higher interfacial energy for the TiO 2 -II phase than for the baddeleyite phase, while the TiO 2 -II → TiO 2 -OI phase transition shows only a minor size dependency.…”
Section: Pressure-induced Inorganic Np Atomic Structure Phase Transitionmentioning
confidence: 99%